Most patients with minimal histological residuals of gastric MALT lymphoma after successful eradication of Helicobacter pylori can be managed safely by a watch and wait strategy: experience from a large international series. Issue 12 (16th July 2007) - Fischbach, W; Goebeler, M E; Ruskone-Fourmestraux, A; Wündisch, T; Neubauer, A; Raderer, M; Savio, A
Abstract : Background: Eradication of Helicobacter pylori is the established initial treatment of stage I MALT (mucosa associated lymphoid tissue) lymphoma. Patients with minimal persisting lymphoma infiltrates after successful eradication of H pylori are considered treatment failures and referred for radiation, chemotherapy, immunotherapy, or surgery. Aim: To report a watch and wait strategy in such patients. Methods: 108 patients were selected from a larger series of patients treated at various European institutions. Their mean age was 51.6 years (25 to 82), and they were all diagnosed as having gastric marginal zone B cell lymphoma of MALT type stage I. After successful H pylori eradication and normalisation of the endoscopic findings, lymphoma infiltrates were still present histologically at 12 months (minimal histological residuals). No oncological treatment was given but the patients had regular follow up with endoscopies and multiple biopsies. Findings: Based on a follow up of 42.2 months (2–144), 102 patients (94%) had a favourable disease course. Of these, 35 (32%) went into complete remission. In 67 (62%) the minimal histological residuals remained stable and no changes became evident. Local lymphoma progression was seen in four patients (5%), and one patient developed a high grade lymphoma. Conclusions: Most patients with minimal histological residuals of gastric MALT lymphoma after successful eradication of H pylori had a favourable disease course without oncological treatment. A watch and wait strategy with regular endoscopies and biopsies appears to be safe and may become the approach of choice in this situation. Longer follow up is needed to establish this definitively.